Maracatu pelas mãos de mulheres: Histórias e Memórias encruzadas pelo Axé, Resistência e Militâncias no Baque Mulher - ARAÚJO, Héveny Daniele Silva (2020)
This research shows the performance of percussionists women in Maracatu Baque Mulher - group idealized and founded by Mestra Joana Cavalcante, the first woman in the world to conduct a nação de maracatu, the Maracatu Nação Encanto do Pina, located in Bode Community, periphery of Recife / PE. Who said women cannot play the drums? Not only do they play, they are also led by a woman conductor. This investigation seeks to understand these women's representations and discourses on musical materiality - that is, to observe how these percussionist women constitute their identities and resignify their trajectories of resistance through Maracatu Nação music and how they militate against machismo, racism, religious intolerance, among others. Methodologically, I carried out a literature review and also an immersion in the field, a process of participant observation (researcher-percussionist) which provided rich experiences and a better acquaintance with these women. I also conducted semistructured interviews, photographic and audiovisual records during the events and concerts of Maracatu Baque Mulher. In view of the complexity of this cultural manifestation, which is based on Candomblé Nagô, promoted mostly by peripheral black communities, who keep in their collective memories moments of resistance and struggle, a theoretical intersectionality perspective was adopted from the discussions of Black Decolonial Feminism theorists to embrace the experiences that are embedded in social markers of inequality. In addition to this, I approached the Ethnomusicologic studies to present Maracatu Nação musical practice as social processes constituted by women in their diversity - political people who hand in hand become a Baque Virado Feminist Movement to fight against oppressive demands of a white cisheteropratriarcal society, which erases and/or makes women's bodies invisible, most of them being peripheral black women.